THE SHIFTING OF ISLAMIC HERITAGE FROM EDUCATION CENTER TO WORSHIP TOMB (THE EFFECT OF THE POLITICAL POLICY) - Indrawati Indrawati; N Nurhasan; Sugiono Soetomo (Journal of Islamic Architecture, 2022)
Many Islamic heritages are not well maintained. This condition also occurs in the Ki Ageng Majasto cemetery, an Islamic heritage site near Surakarta City, Central Java. The function of the area has changed, from the education area in the early time into the Worship Tomb in the present. Therefore, it is important to investigate to find out: (1) Why there was a shift in the function of the area (from an educational area to a worship tomb); (2) what factors influenced it; and (3) What the impact on the regional constellation is. The systematic steps of the grounded research approach are used in this research. After the analysis carried out, it was discovered that the shifting function from the Education area to the Worship Tomb in Majasto Village occurred: (1) when KAM, which functions as the Islamic guardian, has died; (2)  The influence of political factors are dominated in the past (The Pajang I King) although the present governments are Sukoharjo Regency and Majasto Village Government; (3)  The changing of function has its implications for the development of the functions of area and agglomerations as well as regional constellations. This finding provides direction on the importance of documenting historical information in determining regional/urban planning policies.